Strategi Bertahan Hidup Keluarga Buruh Nelayan di Desa Sondana Kecamatan Bolaang Uki, Kabupaten Bolaang Mongondow Selatan - Gobel, Dita Inda Sari; Hatu, Rauf A.; Bumulo, Sahrain (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2024)
This study aims to identify the factors, influences, and strategies employed by fishing laborer families in Sondana Village, Bolaang Uki District, South Bolaang Mongondow Regency, to sustain their daily lives. Sondana Village is a coastal area where 15% of the population works as fishermen and heavily depends on marine resources. However, the decline in fish catches and low selling prices have weakened the economic condition of these fishing families. This research uses a qualitative descriptive method with data collected through observation, interviews, and documentation. The results reveal that fishing laborer families employ various survival strategies: 1) active strategies, including seeking side jobs and involving family members to earn additional income; 2) passive strategies, such as saving or setting aside part of their income for urgent needs; and 3) network strategies, utilizing relationships with boat owners, the government, relatives, or neighbors to borrow money or receive assistance. This study provides new insights into how fishing laborer families adapt to economic challenges and highlights the importance of social support in their survival strategies.